2009
DOI: 10.1159/000238118
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Evaluation of the Amount of Wharton’s Jelly and the Umbilical Coiling Index

Abstract: Objectives: To investigate the association between the amount of Wharton’s jelly (WJ) and the umbilical coiling index (UCI). Methods: The subjects included 140 pregnant women in the 2nd or 3rd trimester. The antenatal UCI was calculated as the reciprocal of the distance between a pair of coils. The sonographic cross-sectional areas of the cord, arteries and vein were measured. The WJ area was calculated by subtracting areas of the total vessels from the cord. Results: UCIs were significantly smaller and WJ are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Degani et al 5 found that the antenatal UCI is higher than the postnatal UCI (0.44 ± 0.11 vs. 0.28 ± 0.08; P < 0.001). Furthermore, the antenatal UCI is lower in the third trimester than in the second trimester16. We found that the 90 th , 50 th and 10 th percentiles of the UCI were 0.578, 0.370 and 0.226, consistent with previous work13.…”
Section: Discussionsupporting
confidence: 91%
“…Degani et al 5 found that the antenatal UCI is higher than the postnatal UCI (0.44 ± 0.11 vs. 0.28 ± 0.08; P < 0.001). Furthermore, the antenatal UCI is lower in the third trimester than in the second trimester16. We found that the 90 th , 50 th and 10 th percentiles of the UCI were 0.578, 0.370 and 0.226, consistent with previous work13.…”
Section: Discussionsupporting
confidence: 91%
“…These results were exactly the ones found in the present study. On the other hand, a recent study did not find any correlation between the WJ area and de Umbilical Coiling Index during pregnancy [20]. …”
Section: Discussionmentioning
confidence: 98%
“…Throughout the entire pregnancy, the total length of umbilical cord is increased, and particularly, in the later period of pregnancy, the length of umbilical cord becomes longer every month by approximately 3 - 6 cm 6. A tendency is that the UCI becomes smaller in the third trimester in comparison with the second trimester7. Nonetheless, the level of the lengthening of umbilical cord varies in each fetus, and thus the change of UCI is individual.…”
Section: Introductionmentioning
confidence: 99%